Insights into the molecular dynamics in polysulfone polymers from C-13 solid-state NMR experiments - Eldho, Kavalakal Mathai; Rajamohanan, P. R.; Anto, Ralf; Bulakh, Neelima N.; Lele, Ashish K.; Ajithkumar, Thalasseril G. (Journal of Physical Chemistry B, 2015)
The molecular and segmental motions in three different grades of ductile polysulfone polymers; poly(ether sulfone) (PESU), polysulfone (PSU), and poly(phenyl sulfone) (PPSU) are probed using C-13 solid-state NMR experiments. Polarization inversion spin exchange at magic angle (PISEMA) experiments indicates that the phenyl rings in the polymers are undergoing pi-flip motions on the order of 100 kHz. The temperature dependent PISEMA experiments show that the fraction of mobile regions that undergoes aromatic pi-flips is higher in PPSU than in the other two polymers. The center band only detection of exchange (CODEX) experiments was carried out and was unable to detect any slow segmental motions in the chains. A combination of C-13 spin-lattice relaxation time (T-1) and T-1-filtered PISEMA experiments show that the mobile regions in all the polymers are dynamically heterogeneous.

1000-fold enhancement in proton conductivity of a MOF using post-synthetically anchored proton transporters - Shalini, Sorout; Dhavale, Vishal M.; Eldho, Kavalakal Mathai; Kurungot, Sreekumar; Ajithkumar, Thalasseril G.; Vaidhyanathan, Ramanathan (Scientific Reports, 2016)
Pyridinol, a coordinating zwitter-ionic species serves as stoichiometrically loadable and non-leachable proton carrier. The partial replacement of the pyridinol by stronger hydrogen bonding, coordinating guest, ethylene glycol (EG), offers 1000-fold enhancement in conductivity (10(-6) to 10(-3) Scm(-1)) with record low activation energy (0.11 eV). Atomic modeling coupled with C-13-SSNMR provides insights into the potential proton conduction pathway functionalized with post-synthetically anchored dynamic proton transporting EG moieties.

Molecular motifs for additives that retard PEO crystallization - Shrivastava, Sudhakar Dinesh; Eldho, Kavalakal Mathai; Rajamohanan, P. R.; Ajithkumar, Thalasseril G.; Vanka, Kumar; Kumaraswamy, Guruswamy (Polymer Engineering & Science, 2017)
We investigate the influence of several bifunctional phenol additives (resorcinol: RES, hydroquinone: HYD, p-hydroxybenzoic acid: PHBA, and p-nitrophenol: PNP) on the crystallization of matrix polymer, polyethyleneoxide. We employ solid state Nuclear Magnetic Resonance spectroscopy (NMR), Differential Scanning Calorimetry (DSC), optical microscopy, and Small Angle X-ray Scattering (SAXS) to investigate crystallization of the additivated PEO and compare with Density Functional Theory (DFT) calculations of additive-PEO interactions. Additive-polymer interactions are a function of the functional groups on the additive. Temperature-dependent spherulitic growth rate measurements from optical microscopy and SAXS lamellar long spacings indicate a distinct trend in the effect of additives on PEO crystallization. Change in PEO crystallization is most pronounced with PNP, followed by PHBA and finally RES and HYD. This trend correlates qualitatively with the binding energies of additive-PEO interactions from DFT studies. Our results suggest that DFT calculations might be a useful screening tool to evaluate the influence of additives on polymer crystallization. POLYM. ENG. SCI., 2016. © 2016 Society of Plastics Engineers